Implementasi Kebijakan Sekolah Dalam Menanggulangi Kenakalan Siswa Di SMA Negeri 9 Kota Bengkulu Tahun Ajaran 2025/2026 - Oktariana, Fahmi; Syarkati, Syarkati (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study examines the implementation of school policies in addressing student delinquency at SMA Negeri 9, Bengkulu City. The purpose of this study was to determine the forms of student delinquency, to determine the established policies, and to identify the factors inhibiting and supporting the implementation of school policies in addressing student delinquency at SMA Negeri 9, Bengkulu City. This study is a qualitative study. Data collection in this study was conducted using observation, interviews, and documentation techniques. This study yielded the following findings: The results of this study indicate that forms of student delinquency at SMA Negeri 9 Bengkulu City include truancy, arriving late to school, untidy clothing, wearing a uniform, incomplete attributes, smoking, excessive use of accessories and makeup, fighting, ganging up, forming motorcycle gangs, sleeping in class, wearing bracelets and necklaces for boys, carrying sharp objects, teasing friends, having long and dyed hair, not attending flag ceremonies, and using foul language. The school policy established at SMA Negeri 9 Bengkulu City is to use an individual approach. In handling cases of student delinquency, the homeroom teacher/BP teacher first calls the child for guidance and direction. This parent summons is intended to inform parents at home what their child is doing after school. Currently, this parent summons policy can be considered effective. However, there are still inhibiting factors, namely parents who do not accept if their children are wrong, Second, the lack of support from the government regarding policies set by schools, the government is also less proactive in receiving reports from parents regarding policies set by schools, with this impact returning to the school. Meanwhile, the supporting factors are first, support from some parents who entrust their children to be educated at school and do not side with their children when their children are caught doing wrong, Some of these parents accept and are able to take responsibility for the mistakes their children make. Second, support from the principal, teachers, homeroom teachers, student affairs, BP / BK who work together in discussions about school policies in accordance with government regulations.